2016
DOI: 10.1136/bmjopen-2016-013246
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of taste and smell impairment in a nationwide representative sample of the US population: a cross-sectional study

Abstract: ObjectivesTo estimate the prevalence of, and explore potential risk factors for, taste and smell dysfunction in the general population of the USA.DesignA cross-sectional study.SettingA cross-sectional analysis of data collected in the National Health and Nutrition Examination Survey (NHANES 2013–2014).ParticipantsA total of 3519 men and women aged 40 years and older who participated in NHANES 2013–2014.Main outcome measuresUsing the NHANES Pocket Smell Test, smell impairment was defined as failing to correctly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
174
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 51 publications
12
174
0
1
Order By: Relevance
“…In our study cohort, we found significantly higher rates of comorbidities and other medical conditions in adults with alterations in smell or taste. This is consistent with previous studies analyzing national surveys on this topic . Persistent cold/flu symptoms, sinonasal disease, and head trauma have been reported as being associated with olfactory and gustatory dysfunction likely due to disruption or obstruction of the olfactory mucosa .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study cohort, we found significantly higher rates of comorbidities and other medical conditions in adults with alterations in smell or taste. This is consistent with previous studies analyzing national surveys on this topic . Persistent cold/flu symptoms, sinonasal disease, and head trauma have been reported as being associated with olfactory and gustatory dysfunction likely due to disruption or obstruction of the olfactory mucosa .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies analyzing national surveys on this topic. 32,33 Persistent cold/flu symptoms, sinonasal disease, and head trauma have been reported as being associated with olfactory and gustatory dysfunction likely due to disruption or obstruction of the olfactory mucosa. [1][2][3]8 Comorbidities and exposure to environmental toxins such as smoking and alcohol also likely increase the risk of damage to the olfactory mucosa leading to dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve healthy female Korean participants (mean age, 31.2 years; range, 21‐39 years) who did not exhibit any olfactory diseases participated in this study. The participants were instructed to avoid meals and alcohol six hours before the start of the study, and to not apply any hair products including cosmetics with fragrance . The purpose and relevant information regarding the study were provided to the participants and each provided consent.…”
Section: Methodsmentioning
confidence: 99%
“…Aromatherapy is often referred to as an action using essential oils that contain fragrances extracted from therapeutic plants, to increase mental functioning . It is a natural remedy using plants and performed widely through massage, inhalation, fomentation, bath, and foot bath .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation